THE THEORETICAL-METHODOLOGICAL SIGNIFICANCE OF THE STAGES OF THE MULTI-YEAR TRAINING SYSTEM IN THE SPORTS SELECTION PROCESS - Usmanov Boburjon Komiljon o'g'li (Western European Studies, 2026)
This article explores the profound theoretical and methodological implications of the multi-year training system's stages within the sports selection process. It delves into the foundational principles that underpin long-term athlete development, emphasizing how structured stages facilitate talent identification, skill acquisition, and performance optimization. By integrating insights from pedagogy, physiology, psychology, and sports science, the discussion highlights the necessity of a phased approach to mitigate risks such as burnout, injury, and premature specialization. The analysis underscores the role of these stages in fostering holistic athlete growth, ensuring adaptability to competitive demands, and contributing to sustainable sporting excellence. Through a comprehensive examination of conceptual frameworks, empirical evidence, and practical applications, the article argues for the integration of multi-year training paradigms in sports selection to enhance both individual and systemic outcomes in high-performance sports.
Keywords: Sports selection; multi-year training system; long-term athlete development